Sunni-Shi'ah Islamic Conflict after the Arab Spring: Religious Conflict in the Middle East in the Contemporary Era - Putri, Amelia; Subakti, Ganjar Eka (FALASIFA : Jurnal Studi Keislaman, 2024)
The aim of writing this article is to analyze the Sunni-Syi’ah conflict after the Arab Spring. The method used in writing this article is a qualitative method with technical data collection using literature studies. Sunni and Syi’ah groups are the largest Islamic groups in the world which often experience differences and contradictions regarding their views. them in Islamic teachings, especially in theological and political views. Sunni-Syi’ah conflicts have occurred even since after the Prophet sallallaahu alaihi wa sallam until now. This conflict has had a big influence on political turmoil in the Middle East, especially after the Arab Spring. Various conflicts in various Middle Eastern countries such as Iraq, Iran, Saudi Arabia, Lebanon, Syria, Yemen, and others are not apart from the issue of the Sunni- Syi’ah conflict. Even though the Sunni-Syi’ah conflict is not the main factor in the occurrence of various political upheavals in the Middle East, the issue of this conflict is always an accompaniment to every political upheaval in the Middle East